Effect of salinity on growth and chemical composition of Thalassiosira pseudonana (Hasle & Heimdal, 1970) - Le Trang, Tran Thi (Academia Journal of Biology, 2014)
In aquaculture, Thalassiosira is used to feed to shrimp and shellfish larvae in hatcheries. It is considered preferable for this purpose to the other commercially available microalgae, Chaetoceros and Tetraselmis, because of its larger size which means it can continue to be used at more advanced larval stages. Salinity is one of the environment factors effected significantly on growth and chemical composition of this algae. The experiment was conducted with 6 salinities: 25, 30, 35, 40, 45 and 50‰ in order to identify the optimum salinity for growth and chemical composition of Thalassiosira pseudonana in the laboratory condition. Results showed that: algae was culture in salinity of 30 and 35‰ gave the highest maximum density (76.90 and 78.83 ´ 104 cells/ml), followed by 25‰ (67.87 ´ 104 cells/ml) in the same day 5 and the lowest at 40, 45 and 50‰ (65.33; 60.60 and 55.67 ´ 104 cells/ml) in the day 6 (p<0,05). Specifically, the highest protein, carbohydrate and lipid contents of T. pseudonana were gained at salinity of 25‰ (305.00; 264.33 and 219.33 mg/g), followed by 30 and 35‰ (283.33; 246.67 and 205.33; 274.33; 208.67 and 201.33 mg/g) and the lowest at 40, 45 and 50‰ (245.33; 191.33 and 158.33; 218.33; 18.33 and 144.67; 181.00; 177.33 and 139.67 mg/g) (p<0,05). From the results of this study, it can be suggested that T. pseudonana should be culture at the salinity from 25 to 35‰ to obtain the optimal values of growth and chemical composition.